Engineering and Mathematical Topics in Rainfall 2018
DOI: 10.5772/intechopen.74743
|View full text |Cite
|
Sign up to set email alerts
|

Landslide Susceptibility of Chittagong City, Bangladesh, and Development of Landslides Early Warning System

Abstract: Chittagong, the second largest city of Bangladesh, is mostly developed in the hilly areas. Hills are mostly covered with loose and weathered tertiary sedimentary rocks susceptible to landslides. Generally, during heavy rainfall within a short time, water infiltrates into the loose rocks and soils, which increase the pore water pressure, and finally exceeds the shear strength of the materials to initiate landslides. Landslides history, slope characteristics, geology and geotechnical properties have been conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…2). The current threshold value for landslide occurrence is 300 mm and 200 mm for antecedent rainfall for 3-days and 1-day, respectively (Ali et al 2018). During this event, antecedent rainfall for 3-days and 1-day was less…”
Section: Rainfall Pattern Analysismentioning
confidence: 85%
“…2). The current threshold value for landslide occurrence is 300 mm and 200 mm for antecedent rainfall for 3-days and 1-day, respectively (Ali et al 2018). During this event, antecedent rainfall for 3-days and 1-day was less…”
Section: Rainfall Pattern Analysismentioning
confidence: 85%
“…Studies exist where the global rainfall threshold and rainfall threshold for selected climatic zones are well established (e.g., Idrogeologica et al, 2010;Guzzetti et al, 2010;Nazionale et al, 2007). Only a few studies previously tried to estimate the rainfall threshold for Chittagong city (Khan et al, 2012;Ali et al, 2018). However, a rainfall threshold determination attempt is taken for the Cox's Bazar district employing multiple empirical approaches to cross-validate and thus fine-tune the threshold estimation effort.…”
Section: Discussionmentioning
confidence: 99%
“…We also tried comparing our threshold estimation with similar studies in the Chittagong hill tracts. Ali et al (2018) found that the threshold values for landslides in Chittagong City are 100 mm of rainfall in 3 hours, 200 mm in 24 hours, and 350 mm in 72 hours. This research also indicates that 100mm of rainfall is required to start an event, whereas our study (table 2) reveals that the susceptible rainfall according to maximum threshold value is 34.1mm in 3 hours, 208mm in 24 hours, and 540mm in 72 hours.…”
Section: Threshold Estimation Validation and Research Limitationsmentioning
confidence: 99%
“…Regarding the angle of the slope, it is found that in the landslide-prone areas of Chittagong, the angle ranges between 34 degrees and 84 degrees; most of them are more than 40 degrees. Several man-made factors such as cutting down the hills and changing the shape of the hills, deforestation, and inadequate drainage system are significantly responsible for this situation (Ali et al, 2018). Fatema (2019) has listed all the areas that are prone to the risk of landslides in Chattogram City based on their severity.…”
Section: Landslide Vulnerability Of Chattogrammentioning
confidence: 99%